The Complexity of Economies and Pluralism in Economics - Claudius Gräbner (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
From the two premises that (1) economies are complex systems and (2) the accumulation of knowledge about reality is desirable, I derive the conclusion that pluralism with regard to economic research programs is a more viable position to hold than monism. To substantiate this claim I discuss an epistemological framework of how scholars study their objects of inquiry and relate their models to reality. Furthermore, I argue that given the current institutions of our scientific system, economics self-organizes towards a state of scientific unity. Since such a state is epistemologically inferior to a state of plurality, critical intervention is desirable.
Keywords: A1; A2; B4; 330; Complexity; Pluralism; Epistemology; Cumulative Causation